가변적 서사성과 나선형 표현 방법을 통한 자기 주도적 디자인 교육 - 김한솔; Kim Han Sol; 안병학; Ahn Byung Hak (기초조형학연구, 2018)
시대에 담긴 중요한 사회문화적 관념과 현상을 대변하는 시각문화는 점차 다양성의 견해를 지지하는 방향으로 변하고 있다. 이러한 변화는 디자인에 대한 최종 평가를 주로 디자인을 소비하는 소비자가 수행하던 기존 관념에서 벗어나 디자인의 대상이 되는 문제를 디자이너 스스로 발견하고 표현하려는 경향으로 드러난다. 이 연구는 연구자가 주장하는 디자인 교육이 이런 변화를 어떻게 수용할 수 있는지, 그 실효성에 대한 탐구이다. 이를 위해 먼저 관련 문헌 연구를 통해 디자인 프로세스에서 아카이빙의 중요성, 서사의 가변적 성분과 능동적 시각 수용, 점진적 반복과 나선형 사고에 대해 고찰하고 이를 바탕으로 기획한 가변성과 능동성 진작 프로그램을 실제 수업에 적용했다. 실험은 프로세스 전반에 대한 이해를 행동으로 경험할 수 있는 워크숍으로부터 시작해 ‘개인의 관심사’를 대상의 외적 속성과 내적 속성에 주목해 주제화하고 시각화하기 위해 과정의 순환을 유도한 ‘점진적 반복’으로 이어졌다. 이어 이 모든 과정을 하나의 서사적 흐름으로 묶어내게 하는 단계를 거쳤고, 끝으로 수용자의 새로운 해석과 의미 재생산을 통해 문제의식을 공유하게 하는 ‘타인의 이해’ 단계로 이동했다. 그 결과 가장 먼저, 점진적이고 동태적 반복을 통한 디자인 교육이 과정 그 자체의 심화를 가능하게 함을 확인할 수 있었고, 학생 스스로 작업에 대한 자기 판단을 유도하는데 효과적인 방법임을 확인할 수 있었다. 더불어 디자이너가 생산한 시각 결과물에 대한 타인의 이해를 높이기 위한 장치를 마련하는 과정에서 이미지 생산 이후 생겨나는 문제에 대한 자각과 이해를 높임으로써 능동적이고 주체적인 문제 해결에 대한 접근을 유도할 수 있었다. 종합하자면, 이 연구를 통해 연구자가 시각문화적 관념과 현상을 반영하기 위해 설계한 디자인 교육 프로그램이 시각 언어에 대한 물리적 학습뿐만 아니라 변화하는 디자인 환경에 대한 이해, 그리고 이에 필요한 사고의 틀과 태도를 동시에 교육하는데 매우 효과적이라는 사실을 확인했다. The study argues that the existing notion of the final evaluation system of the design by consumers who mainly consume the design outcomes should be changed. This study reflects this point of view on design education program and explores how it can affect student's attitude as a practical design methodology. The process of the study is as follows: First, through the examination of related references, the study analyzed the importance of the flexible composition of narrative, progressive repetition, and spiral thinking. Second, the analysis led to designing education program targeted for increasing the flexible narrative and spiral method of expression and applied it to actual education fields. The program starts with a workshop where participants could gain an understanding of the process as a whole. Then, drove the 'personal interest' into 'progressive repetition', which led to the circulation of the process in order to visualize and focus on the external and internal attributes of the subjects. In the end, the program went through a phase that led to the grouping of all these processes into an epic stream, before moved to the 'understanding of others' stage, which allowed the audience to share their awareness through new interpretation and meaning reproduction. As a result, the study reached the confirmation how effective the program was to educate not only the physical learning of the visual language but also the thought and attitude that are necessary for it.